2004
DOI: 10.2527/2004.8282375x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper, zinc, and manganese supplementation and source on reproduction, mineral status, and performance in grazing beef cattle over a two-year period123

Abstract: Crossbred, multiparous beef cows (n = 178 in Year 1; n = 148 in Year 2) were used to evaluate the effects of Cu, Zn, and Mn supplementation and source on reproduction, mineral status, and performance in grazing cattle in eastern Colorado over a 2-yr period. Cows were stratified by expected calving date, age, BW, BCS, and liver mineral status and assigned to the following treatments: 1) control (no supplemental Cu, Zn, or Mn); 2) organic (ORG; 50% organic and 50% inorganic Cu, Zn, and Mn); and 3) inorganic (ING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 21 publications
3
47
4
2
Order By: Relevance
“…Similar observations have been reported by other workers [18,8,19], suggesting better nutrient utilization. Higher plasma levels of Cu and Zn in ewes fed Cu-and Zn-methionine was attributed to better gut absorption of these minerals.…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations have been reported by other workers [18,8,19], suggesting better nutrient utilization. Higher plasma levels of Cu and Zn in ewes fed Cu-and Zn-methionine was attributed to better gut absorption of these minerals.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, in the CON group, there was a marked (P<0.05) increase from 0.063±0.02 g/dl to 0.40±0.06 g/dl on day -10 to Day zero, respectively. In this respect, it is reported that the low circulating levels of Mn in cattle lead to silent heat, lower pregnancy rates and abortion (Ahola et al, 2004). In our study, however, no marked reduction in Mn levels was observed in any group.…”
Section: Minerals Valuescontrasting
confidence: 73%
“…Zn and Cu are needed in sufficient quantities to promote good health and to optimize production and reproduction [11,12]. A deficiency of Zn is associated with a loss of appetite, impaired reproduction and testicular development, growth depression, and impaired immune status [10,[13][14][15][16][17]. In dairy cows, low Zn leads to low milk quality with high somatic cell count and an increased incidence of mastitis [18] and other diseases [19].…”
mentioning
confidence: 99%